The Effect of Using Genre-Based Approach towards Students’ Writing Skill on Recount Text - Devia Della Dhika; Muhammad Sulhan (JEdu: Journal of English Education, 2021)
The research aims at determining the effect of using Genre-Based Approach towards students’ skill on writing recount text at SMP PGRI 9 East Jakarta. It uses quantitative design by giving treatment of the application of Genre-Based Approach to the experiment class. The population was all students of eight graders at SMP PGRI 9 East Jakarta and was taken 50 of them as the samples. They were divided into two classes; the experiment class consists of 25 students and the control class consists of 25 students. The result shows that the mean of the control class is 69.78, the median is 70, and the mode is 65.94 with standard deviation values is 7.63. While, the mean of the experiment class is 81.06, the median is 81.35 and the mode is 101.5 with standard deviation values is 10.1. The Fobserved is 1.78 < Ftable 1.98, meaning that both classes are homogenous. The hypothesis test tobserved is 4.44 > ttable 2.01, which means that H1 is accepted which confirms there is an effect of using Genre-Based Approach towards students’ writing skill on recount text at SMP PGRI 9 East Jakarta.